Implementation of Occupational Health and Safety Standards for Office Buildings in Universitas Airlangga Rectorate Building - Dinda Pratiwi; Dani Nasirul Haqi; Herman Bagus Dwicahyo (Universitas Airlangga, 2022)
Introduction: Universitas Airlangga office building rectorate includes a high-rise building that must have occupational health and safety (OHS) facilities and also its application must be in accordance with office building standards which applies to prevent accidents and occupational diseases. This study aims to determine OHS office buildings rectorate facilities, and to analyze OHS standards application for office buildings rectorate with applicable OHS office building standards. Methods: This research is an observational study. Data analysis using descriptive method with a cross sectional study design. The variables studied were OHS office building facilities in Universitas Airlangga Rectorate, and OHS standard application for in Universitas Airlangga office buildings rectorate. Data collection techniques are derived from primary data in OHS observations form facilities in office buildings and secondary data in agency documents form. Results: Work safety facilities include fire extinguishers, hydrants, evacuation routes, evacuation plans, gathering points, first aid kits. emergency stairs, safety sign. Occupational health facilities include health promotion media, workforce health checks, and lactation rooms. Office work environment health facilities include toilets and hand washing facilities. Then office ergonomics facilities include cushions for employee work chairs. Conclusion: The facilities are in accordance with Republic of Indonesia Health Minister Regulation Number 48 of 2016 concerning Office OHS Standards which include occupational safety application, occupational health, and office environmental health standards and office ergonomics. The implementation of OHS standards for office buildings at in Universitas Airlangga Rectorate, such as occupational safety, occupational health, office work environment health, and office ergonomics standards have been implemented and carried out.